Perspective View on Sorption Thermodynamics: Basic Dye Uptake on Southern Nigerian Clay - Emeniru, Daniel C.; Neminebor, John; Ikirigo, Justin; Sogbara, Franklin (European Scientific Journal, ESJ, 2017)
Macroscopic phenomenon like adsorption has a mechanistic tie typical of thermodynamics and its principles. This work examined the thermodynamic parameters for methylene blue (MB) uptake onto modified Ekowe clay (EC). The purified clay was calcined for 4hrs. at 750 oC to obtain Natural Ekowe Clay (NEC). The purified clay was activated (1.6M H2SO4 (aq)) and calcined for 4hrs. at 750 oC obtaining Activated Ekowe Clay (AEC). Thermodynamic study applied the equilibrium data in determining the activation and heats of adsorption parameters. The concave Eyring plot suggests more than one rate-limiting steps coexisting in the sorption. For temperatures: 25, 30 and 40 oC, activation energies (3) for NEC and AEC lie between 2 - 29kJ/mol inferring physisorption. Negative activation enthalpies (ΔH * ) values confirm exothermic activations. The less negative ΔH * values, in compliance with the significant k2 values varying inversely with temperature, suggests high sorption rate. The negative activation entropy explained an associative uptake and the less negative values are attributive to a physical uptake. Negative free activation enthalpy, ΔG * indicated that uptake on the modified EC is spontaneous. High negativity of ΔG * values suggest strong physic-sorption bond. The negative ΔH * , ΔS * and ΔG * values characterize the physisorption of MB onto modified EC. Values of the isoexcess heats (qisox) obtained: 2.67kJ/mol. (NEC) and 2.47kJ/mol. (AEC) agreed with the value range of <80kJ/mol. typical to physic-sorption. This work opines that sorption of MB onto modified EC is a spontaneous exothermic multilayer phenomenon that progresses heterogeneously with continuous decrease in sorption potential and fall in isosteric heat.